Investigation of equivalent length of several polypropylene compression fitting use in domestic plumbing [electronic resources] - Ong, Chong Lih, 1988- (2012)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2012